The factors that influence housing demand in Kuala Lumpur from perspective interest rate and house price / Sharizan Omar - Omar, Sharizan (2007)
This research is to examine the factors correlated with house demand in Kuala Lumpur from perspective interest rate and house price quarterly from 1999 to 2006. This study will be using multiple regression and correlation coefficient method. Therefore, it will investigate an interest rate relationship with the housing demand in Kuala Lumpur and the house price relationship with the housing demand in Kuala Lumpur. This research has used exploratory study to clarify and define the nature of problem identification where in this study we want to identify the correlation of interest rate and house price to housing demand in Kuala Lumpur. From the finding, show the house price and interest rate have the relationship with the housing demand in Kuala Lumpur. Meanwhile the test for the regression show that only interest rate is have the effect to the housing demand in Kuala Lumpur but the house price is do not have the effect to the housing demand in Kuala Lumpur.